The effect of high temperature deformation on the austenite reversion transformation and η-Ni3Ti precipitation behavior in a Ti–Mo maraging steel - Chih-Yuan Chen; Iting Chiang; Yung-Chang Kang (Journal of Materials Research and Technology)
Via microstructural characterization analysis and mechanical properties tests, the present study primarily focused on exploring the effect of hot deformation strain on the phase transformation behavior in Ti–Mo precipitation hardening stainless steels (PHSSs). Interestingly, under the fixed ageing condition, it was found that more reverted austenite formed when the Ti–Mo PHSSs were subjected to a large amount of hot deformation strain, which could be attributed to the more retained austenite achieved during deep cryogenic treatment. In other words, a positive correlation between retained austenite and reverted austenite prevailed in Ti–Mo PHSS. Furthermore, when the ageing temperature was increased from 520 °C to 640 °C, the KAM distribution lines shifted to higher angles under the lower strain, i.e. ε = 35 %, whereas under large strain (ε = 70 %), the positions of the KAM distribution lines remained at similar sites. This finding implies that higher thermal stability of reverted austenite was achieved when the Ti–Mo PHSS was subjected to large hot deformation strains. The above metallurgical phenomenon was further verified by Vickers hardness measurement. For example, under the fixed ageing temperature of 520 °C, the distributions of HV0.1 values were 480–680 and 370–660, respectively, for Ti–Mo PHSSs subjected to hot deformation strains of 35 % and 70 %, respectively. These results also corroborate the formation of more soft reverted austenite under the larger hot deformation strain.